radicals
posted by troy .
multiply. assume that expressions under radicals are non negative.
√x+3 * √x3

radicals 
Reiny
we know √a * √b = √(ab)
so √(x+3) * √(x3)
= √[(x+3)(x3)]
=√(x^2  9)
Respond to this Question
Similar Questions

Algebra 1
Simplifying Radicals, Use the quotient property to simplify the expression. 3 times the square root of 6/3 3*sqrt(6/3) is the same thing as saying 3*sqrt(2) Your problem: 3√(6/3) is the same as 3√6/√3 To rationalize … 
Algebra 2: Radicals URGENT!!
Could some kind, saintly soul help me solve this problem? 
amth/algebra
can someone help me with simplification: ã20/5  1/ã5 my first answer is 1/ã5 my second answer is 10 ã5/5 but the answere I have to choose from are: (a) ã20  5ã5/ã5 (b) ã20  ã5/5 (c) cannot be simplified … 
ALGEBRA
Multiply & simplify Assume that all expressions under the radicals represent non negative numbers... √5x^7 √35x 
ALGEBRA
add then simplify.by collecting like radical terms if possible assuming that all expressions under radicals represent non negative numbers: √5a + 2√45a^3 
Math SCREAMING for HELP
Use the quadratic formula to slove the equation. x^2x=7 This is what I have got so far and I do not think this is right: x=1(1)±√1^24(1)(7)/2(1) x=1±√14(7)/2 x=1±√21/2 x=1±21/2 and here I am lost! Use … 
Algebra
1) Is the equation: 28  4√2 = 24√2 True? 
Math  Help with radicals please
Please show work Simplify rational 1. 4√(a^6 b^13) / 4√(a^2b) 2.√(2x^3 / 49y^4) Add or Subtract 3. x√(75xy)  √(27x^3y) Multiply 4.(√(5)  5) (2√(5) + 2) Rationalize the denominator 5. √(25x^5 … 
algebra
Multiply and simplify. Assume that no radicands were formed by raising negative numbers to even powers. √6x^3 * √18x^2 = √2 * 3 * x^3 * √2 * 3^2 * x^2 = √2 * 3x^2x * √2 * 3^2 * x^2 = 6x^2 * √3x … 
algebra
Multiply and simplify. Assume that no radicands were formed by raising negative numbers to even powers. √6x^3 * √18x^2 = √2 * 3 * x^3 * √2 * 3^2 * x^2 = √2 * 3x^2x * √2 * 3^2 * x^2 = 6x^2 * √3x …